Tolerance and Reduction of Chromium(VI) by Bacillus sp. MNU16 Isolated from Contaminated Coal Mining Soil - Upadhyay, Neha; Vishwakarma, Kanchan; Singh, Jaspreet; Mishra, Mitali; Kumar, Vivek; Rani, Radha; Mishra, Rohit K.; Chauhan, Devendra K.; Tripathi, Durgesh K.; Sharma, Shivesh (Frontiers in Plant Science, 2017)
The bacterium MNU16 was isolated from contaminated soils of coal mine and subsequently screened for different plant growth promoting (PGP) activities. The isolate was further identified by 16S rRNA sequencing as Bacillus subtilis MNU16 with IAA concentration (56.95 ± 0.43 6μg/ml), siderophore unit (9.73 ± 2.05%), phosphate solubilization (285.13 ± 1.05 μg/ml) and ACC deaminase activity (116.79 ± 0.019 μmoles α-ketobutyrate/mg/24 h). Further, to evaluate the metal resistance profile of bacterium, the isolate was screened for multi-metal resistance (viz. 900 mg/L for Cr, 600 mg/L for As, 700 mg/L for Ni and 300 mg/L for Hg). Additionally, the resistance pattern of B. subtilis MNU16 against Cr(VI) (from 50 to 300 mg/L) treatments were evaluated. An enriched population was observed at 0–200 mg/L Cr(VI) concentration while slight reductions were observed at 250 and 300 mg/L Cr(VI). Further, the chromium reduction ability at 50 mg/L of Cr(VI) highlighted that the bacterium B. subtilis MNU16 reduced 75% of Cr(VI) to 13.23 mg/L within 72 h. The localization of electron dense precipitates was observed in the TEM images of B. subtilis MNU16 which is might be due to the reduction of Cr(VI) to Cr(III). The data of fluorescence microscopy and flow cytometry with respect to Cr(VI) treatments (50–300 mg/L) showed a similar pattern and clearly revealed the less toxic effect of hexavalent chromium upto 200 mg/L Cr(VI) concentration. However, toxicity effects were more pronounced at 300 mg/L Cr(VI). Therefore, the present study suggests that the plant growth promoting potential and resistance efficacy of B. subtilis MNU16 will go a long way in developing an effective bioremediation approach for Cr(VI) contaminated soils.